FAKTOR-FAKTOR YANG MEMPENGARUHI KINERJA AUDITOR PADA KANTOR AKUNTAN PUBLIK DI DENPASAR - Ni Komang Dina Sintyawati; Ni Putu Ayu Kusumawati; Ni Wayan Alit Erlina Wati (UNHI Press, 2021)
The purpose of this study was to determine the effect of Auditor Experience, Competence and Independence on Auditor Performance at Public Accounting Firms in Denpasar City. A total of 13 KAPs in Denpasar City with a sample of 122 auditors obtained based on saturated sampling technique, where all populations were sampled. Data analysis techniques include descriptive analysis, validity test, reliability test, classical assumption test, multiple linear regression analysis, F test, coefficient of determination (R2), and t test. The results showed that: (1) Auditor's experience had a negative effect on Auditor Performance, with a regression coefficient of -0.043, a tcount of -0.444 and a significant value of 0.658> 0.05. (2) Competence has a positive effect on Auditor Performance, with a regression coefficient of 0.228, a tcount of 3.103 and a significant value of 0.002 <0.05. (3) Independence has a negative effect on Auditor Performance, with a regression coefficient value of 0.144, a t-count value of 1.576 and a significant value of 0.118> 0.05.